Beyond the Horizon: A 2D Animation Approach to Reducing Mental Health Stigma Among Youth - Ahmad, Muhammad Fazrulhelmi; Ryan Fong,; Muhammad Adam Haikal,; Muhammad Faris Zaqwan, (Multidisciplinary Applied Research and Innovation, 2026)
Depression is a growing concern among youth, yet awareness and empathy remain limited due to stigma and lack of relatable educational resources. This project aims to raise mental health awareness among individuals aged 13 to 25 by developing a 2D animated short film that symbolically portrays the emotional realities of depression. The animation combines visual storytelling, color theory, and sound design to deliver a message that resonates with the target audience. Methodologically, the project applied a mixed approach involving literature review, interviews with individuals who have experienced depression, and a questionnaire distributed to 40 participants. The animation production followed a traditional three-phase pipeline: pre-production, production, and post-production. Results from the survey showed that 86.5% of respondents believed 2D animation was effective in communicating mental health issues, and 92.3% reported experiencing a stronger emotional impact through the medium. Interview data provided metaphors and personal insights that shaped the narrative. Overall, the findings confirm that 2D animation is an impactful and empathetic medium to promote mental health literacy and foster meaningful conversations among youth.